Sobre a ilegitimidade de normas impeditivas do reconhecimento de direitos marcários baseadas em moral, bons costumes, ofensividade e outros juízos de valor sobre o conteúdo da expressão - Barbas, Leandro Moreira Valente (2020)
Article 124, item III, of Brazilian Federal Law number 9.279/1996 (Industrial Property Law) sets forth that the following shall not be registered as trademarks: "expressions, images, drawings or any other signs contrary to morals and good customs or which offend a person’s honor or image or are an affront to the liberty of conscience, beliefs, religious cults or to ideas and sentiments worthy of respect and veneration". We herein label this legal passage as the "morality clause". This work is dedicated to analyze why such regulation - or any other legal text of analogous content, even if partial, that may replace it - is legally intolerable, being illegitimate for contrary to the democratic principles of viewpoint neutrality (value neutral treatment of speech by the State), being unconstitutional for the same motive, under the free speech clause. We discuss the direct relations between trademarks and free speech, making clear how both concepts approach in a way that hindering the registration or legal recognition of a trademark on the basis of a morality clause translates into an open attack on free speech. After a careful study on the topics that surround said theme, we advance to a "case-by-case" analysis of situations in which, from a practical standpoint, the morality clause is applied. These include the use, in trademarks, of profanity and swear words in general; names of illicit drugs; of expressions allegedly offensive to religions; names and symbols of criminal organizations; "hate speech"; among other cases. By the end of the thesis, we advance to study landmark cases related to the topic, originating from jurisdictions such as the United States and Europe, where the arguments we hereby discuss are applied, partially or in whole, either to accept or reject them.